The Critical Thinking Abilities in Learning Using Elementary Algebra E-Books: A Case Study at Public Universities in Indonesia - Mursalin, Mursalin (Malikussaleh Journal of Mathematics Learning (MJML), 2019)
The learning Algebra courses are often taught using coventional textbooks. However, the reality of the learning outcomes has not been able to absorb the material to the maximum extent possible, and this is because the textbooks is limited in number so that students only record some of what is taught by the Lecturer. At the same time, electronic books are available free of charge in several world libraries. The purpose of this study is to determine the ability to think critically mathematically through the use of Elementary Algebra electronic books. The study of the method are used a Quasi Experiment with a nonrandomized Pre-test Post-test Control Group Design research design. The study population was all students who took Elementary Algebra in the Department of Mathematics Education, Malikussaleh University, in the Even Semester 2018/2019 academic year. Sample for the study was students of class A1 as an Experiment group using E-books for Teaching, and Class A2 as a Control group with lectures using conventional textbooks. The results showed that the mathematical critical thinking ability of students taught using Electronic books was better than the mathematical critical thinking ability of students who were taught using conventional textbooks. Thus the use of elementary algebra electronic books (E-books) can improve students' mathematical critical thinking skills in learning Algebra.